Programma: 14 november Blood, Sweat & Tears; 15 november Average White Band; 16 november Selecter; 17 november Dreadzone, Digi Dub; 18-19 november Timemachine
Programma: 14 november Blood, Sweat & Tears; 15 november Average White Band; 16 november Selecter; 17 november Dreadzone, Digi Dub; 18-19 november Timemachine.